Prácticas funerarias durante el Período Colonial Temprano en la iglesia de Huanchaco – valle de Moche. - Ascencio Falla, Jefrin Anthony (2019)
The study of funerary practices in the Church of Huanchaco has allowed us to define the mortuary activities carried out during the Early Colonial Period. These funerary practices are related to the process of evangelization and conquest that took place in the Peruvian territory, however this cultural impact was not developed in the same way in the different cultural points of the Andean world. In this context, the study of the funerary contexts of the early colonial period, located in the church of Huanchaco are defined in two moments: in the first moment, There are two types of practices within the same social group, the first type accepts the ideological canons of the Catholic religion, while the second type still retains features of the pre-Hispanic cosmovision of the north coast. Later, in the second stage, the development of the first type funerary remains, including an advance in Catholic funeral rites, related to strategies to obtain and legitimize their social status.